Mucinous Adenocarcinoma Arising in Chronic Perianal Fistula: Good Results with Neoadjuvant Chemoradiotherapy Followed by Surgery - Marisa D. Santos; Carlos Nogueira; Carlos Lopes (Case Reports in Surgery)
Chronic perianal fistulas are a common clinical condition. However, their evolution to adenocarcinoma is rare. We report the case of a 48-year-old man with perianal chronic fistulas, who developed two perianal ulcerated lesions near the external orifices of the fistulas, which extended proximally as a pararectal tumor. No intestinal lesion was seen at endoscopic examination. Histopathological biopsy indicated mucinous adenocarcinoma. Staging was performed by pelvic magnetic resonance imaging (MRI) and thoracoabdominal CT scan. The patient underwent a laparoscopic colostomy followed by neoadjuvant chemoradiotherapy and then laparoscopic abdominoperineal resection followed by adjuvant therapy. We have seen a favorable outcome with no recurrence at 3 years of follow-up.